ECONOMIC UNCERTAINTY AND AUDITORS’ PROFESSIONAL SKEPTICISM: AN EMPIRICAL STUDY AMIDST GLOBAL VOLATILITY - Tommy Kuncara; Rini Dwiastutiningsih (Asosiasi Dosen Muda Indonesia, 2025)
In times of economic instability, auditors face increasing challenges in maintaining professional judgment and audit quality. This study investigates the relationship between perceived economic uncertainty and auditors’ professional skepticism, while also examining the moderating role of self-efficacy and the mediating role of client pressure. Using a quantitative approach, survey data were collected from 100 external auditors across public accounting firms in Indonesia. The results of regression analysis reveal that higher perceived economic uncertainty significantly reduces the level of professional skepticism. Additionally, client pressure was found to negatively impact skepticism, while self-efficacy exhibited a strong positive effect, acting as a buffer against external pressures. These findings suggest that both environmental and individual-level factors influence auditor behavior during uncertain economic conditions. This study contributes to the behavioral auditing literature by incorporating macroeconomic perceptions into the audit judgment framework and offers practical implications for audit firms and regulators to strengthen auditor resilience and objectivity under pressure.